Hazards associated with the application of gene therapy in sport - Gronek, P.; Lehmann, J.; Laurentowska, M.; Michalak, E.; Domaszewska, K.; Stankiewicz, K.; Rychlewski, T.; Szalata, M.; Slomski, R. (Biology of Sport, 2007)
The principal assumption of gene therapy is to achieve the therapeutic effect by a gene transfer into definite cells. It can be carried out on the entire organism (in vivo therapy) but also on collected cells, after their genetic modification, are returned back to the patient (ex vivo therapy). The therapeutic gene can be introduced using physical, chemical or biological methods. Vectors used in gene therapy are DNA molecules to which, by means of covalent bonds, a fragment of another DNA molecule can be joined and the entire unit can be introduced into the cell of the recipient. In the case of bacteria, plasmids or bacteriophages can serve as vectors, whereas in the case of eukaryotic cells, viral vectors are applied, e.g. papilloma, SV40 (papovaviruse), vaccinia virus, adenoviruses, retroviruses, baculloviruses etc. Genetic doping can be treated as a "splinter" of gene therapy. The prediction is that it is quite possible that on the next Olympic Games in 2008 the first genetically modified sportsmen can appear. Many investigations are focused on the detection of genetic "doping".